Educational study on the effect of unknown time on compromise of Iranian Law and International Documents - Sharbati, Siavash (2021)
The aim of this study was the effect of unknown time on commitment in Iranian law and international documents. Which has been done in a library method and by reviewing the documents. It is reasonable, however, that the implementation of the undertaking in such circumstances in international documents is reasonable and standard. For International Documents: Article 33 of the United Nations Convention on the International Sale of Goods (CISG) International Trade Contracts (UPICC), Article 107-27 of the European Treaty Law (PECL) and Article 102-22 of the DCFR Common Framework of Reference). After concluding the contract, considering all its essential terms and conditions, for any reason, deliberately or unintentionally, one of the parties may refuse to execute the contract on the pretext that the contract is unenforceable, and the civil law seems silent. It does, and there is no explicit solution to our civil law, despite the stipulation in international documents.